Machinability study of ultrasonic assisted machining (UAM) of carbon fibre reinforced plastic (CFRP) with multifaceted tool - Abd Halim, Nor Farah Huda; Ascroft, Helen; Barnes, Stuart (Elsevier, 2016)
This paper discusses the conventional machining (CM) and ultrasonic assisted machining (UAM) of end milling carbon fibre reinforced plastic (CFRP). Tool condition, cutting forces and surface integrity of machined surface were evaluated. A commercially available tool with a diameter of 10mm and a nickel bonded, 420 µm diamond grit coating was used with a constant speed of 565 m/min, feed rate of 1500 mm/min and radial depth of cut of 3 mm. For UAM, a frequency of 43 kHz and amplitude of 6.9 µm were employed. UAM showed a reduction in cutting force,better tool condition and improved of surface roughness as compared to CM.